Safe laparoscopy during COVID-19 pandemic by SARS-CoV-2: bio innovation of the closed-circuit system - Govindaraj, Shrenik; Prakash, Clement; Govindaraj, Sridar (International Surgery Journal, 2021)
Background: Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) transmission during laparoscopy while using energy devices through the carbon dioxide pneumoperitoneum is a big concern in operation theatre. So, we had to alter the way we vent carbon dioxide through a closed-circuit system (CCS) to avoid contamination. Methods: We did a prospective study in the safety of the CCS during elective laparoscopic surgeries. We had recruited 184 patients from a single unit in three quarters. The first quarter had 52 patients where the SARS-CoV-2 status was unknown as rapid antigen test (RAT) and reverse transcription polymerase chain reaction (RT- PCR) was not done as per government guidelines. So, we presumed all patients to be potential carriers. Later in the 2nd and 3rd quarter we had recruited 132 patients; all were tested by RAT/RT-PCR and positive patients were excluded from our study. Postoperatively we observed for COVID-19 symptoms in our health care workers (HCW) and confirmed by RT-PCR. Results: Of the total 184 laparoscopic surgeries performed during this period, only 2 (1.09%) patients developed COVID-19 symptoms and this was in the 1st quarter when routine testing by RT-PCR was not done. None (100%) of our HCW developed symptoms of COVID-19. Conclusions: Closed circuit system is an innovative and safe technique during laparoscopy. We strongly recommend RT-PCR for COVID-19 before elective surgery.